PENGARUH KEPUASAN KERJA DAN IKLIM ORGANISASI TERHADAP KOMITMEN ORGANISASI KARYAWAN STUDI KASUS PT. KURNIA SUBUR DI RENGAT - Srimaulani '; Taufiqurrahman '; Henni Noviasari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine how the influences of job satisfaction and organizational climate on organizational commitment employee case study PT. Kurnia Subur in Rengat. The population in this study wasall employees at PT. Kurnia Subur 86 people. The sampling is done by making all employees in the sample. Analysis of the data used is descriptive analysis with quantitative analysis tools that multiple linear regression with SPSS version 18.00. From the testing that has been done, simultaneous test showed that job satisfaction and organizational climate simultaneously haveeffect to organizational commitment of employees, while the partial test job satisfaction and organizational climate partially have effect to the organizational commitment of employees at PT. Kurnia Subur In Rengat. In order to maximize organizational commitment of employees at PT. Kurnia Subur In Rengat,it is necessary to increase the employee's emotional ties to the company. For example, by giving the employee participation in decision-making regarding the company and with regard to employee in company facilities. It is expeted that employees will have a strong emotional bond with the company and to increase employees' organizational commitment.Keyword : Job Satisfaction, Organizational Climate, Commitment Organization.